A review of the validity of computerized neurocognitive assessment tools in mild traumatic brain injury assessment. (30th January 2017) - Arrieux, Jacques P; Cole, Wesley R; Ahrens, Angelica P
Computerized neurocognitive assessment tools (NCATs) offer potential advantages over traditional neuropsychological tests in postconcussion assessments. However, their psychometric properties and clinical utility are still questionable. The body of research regarding the validity and clinical utility of NCATs suggests some support for aspects of validity (e.g., convergent validity) and some ability to distinguish between concussed individuals and controls, though there are still questions regarding the validity of these tests and their clinical utility, especially outside of the acute injury timeframe. In this paper, we provide a comprehensive summary of the existing validity literature for four commonly used and studied NCATs (automated neuropsychological assessment metrics, CNS vital signs, cogstate and immediate post-concussion and cognitive testing) and lay the groundwork for future investigations.